Efficacy of Endangered Pinto Abalone (Haliotis kamtschatkana) Stock Restoration in the Southern Salish Sea From a Genomic Perspective - Dimond, James L.; Bouma, Joshua V.; Carson, Henry S.; Gavery, Mackenzie R.; O’Brien, Caitlin; Simchick, Crystal; Sowul, Kathleen (Frontiers in Conservation Science, 2022)
Declines in abalone populations throughout the world have led to conservation measures including fishery closures and captive breeding programs aimed at stock restoration. Restoration of endangered pinto abalone (Haliotis kamtschatkana) in the southern Salish Sea (Washington State, USA) began in the mid-2000s, and since 2009, nearly 40,000 hatchery-produced juvenile abalone have been outplanted at 21 restoration sites. We used genotyping by sequencing to evaluate the efficacy of this restoration program from a genomic standpoint. Over 49,000 SNPs and 8,000 haplotypes were evaluated across both wild and hatchery-produced abalone. Compared to wild abalone, hatchery-bred abalone had similar heterozygosity, lower allelic richness and effective population size, and higher relatedness. However, more recently bred hatchery progeny sampled prior to outplanting showed intermediate allelic richness, lower relatedness and genomic divergence, and higher effective population size compared to older hatchery outplants sampled after outplanting. We attribute these differences to genetic drift among older hatchery outplants due to mortality and emigration as well as larger numbers of broodstock families in more recent hatchery operations. This suggests that current hatchery practices that combine higher output with larger numbers of broodstock families may more effectively overcome the effects of genetic drift. Effective population size estimates among wild Salish Sea abalone had no upper limit, indicating that these abalone have sufficient genetic diversity to support the restoration program, but also highlighting the need for large broodstock sizes to overcome potential Ryman-Laikre effects. The greatest challenge for the future of the restoration program will be finding sufficient numbers of wild broodstock in the Salish Sea, where pinto abalone remain extremely rare.